2013
DOI: 10.1177/1010539513496841
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the September 2009 Sumatra Earthquake on Reproductive Health Services and MDG 5 in the City of Padang, Indonesia

Abstract: Indonesia has been making good progress in reproductive health (RH) outcome. This study aimed to examine the effect of the September 2009 Sumatra earthquake on availability and accessibility of RH services and its possible impact on local Millennium Development Goals (MDGs). Twenty-six health facilities in Padang City were reviewed and 667 clients directly interviewed. Water supply shortage was most widespread and slowest to recover, taking more than 1 year to normalize. Antenatal and emergency obstetric care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…Our findings that unwanted pregnancy and a short interpregnancy interval were more common after the earthquake are consistent with unmet contraceptive need, which has been reported anecdotally and confirmed in previous studies of disasters, 34,35 as well in as these data (Do et al, unpublished observations). This finding may be due in part to the lack of availability of family planning services after the earthquake.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings that unwanted pregnancy and a short interpregnancy interval were more common after the earthquake are consistent with unmet contraceptive need, which has been reported anecdotally and confirmed in previous studies of disasters, 34,35 as well in as these data (Do et al, unpublished observations). This finding may be due in part to the lack of availability of family planning services after the earthquake.…”
Section: Discussionsupporting
confidence: 93%
“…A study in Sumatra found that improvements in maternal and infant mortality were stalled by an earthquake and that child mortality and stillbirth rose. 34 High rates of spontaneous abortion, but not congenital anomalies, were reported after the Bhopal gas release in India. 36 An increase in neural tube defects was also noted after Hurricane Gilbert, which was thought to be due to decreased folic acid intake after crop destruction.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…While destruction of hospitals and healthcare facilities led to severe lack of antenatal care, pregnancy rates are paradoxically likely to increase following a disaster due to unavailability of contraceptives and reduced bargaining power in sexual situations 11. And while few studies among pregnant earthquake victims have reported reduced birth weight and increased stillbirth rates,12 13 nutritional deficiency is common among pregnant women in disaster situations, and may be associated with adverse pregnancy outcomes.…”
mentioning
confidence: 99%
“…In the medium term, reproductive outcomes continued to be affected with shorter inter-pregnancy intervals 89 , increases in unplanned pregnancies 89,91 and an overall increase in births 92 . Also reported were reductions in access to reproductive health services as a consequence of the earthquake 91,[93][94][95] .…”
Section: Reproductive Healthmentioning
confidence: 99%